Cover Image. Issue 6 (June 2017) - El‐Heis, S.; Crozier, S. R.; Healy, E.; Robinson, S. M.; Harvey, N. C.; Cooper, C.; Inskip, H. M.; Baird, J.; ,; Godfrey, K. M.
Abstract : The cover image, by S. El‐Heis et al., is based on the Original Article Maternal stress and psychological distress preconception: association with offspring atopic eczema at age 12 months, DOI10.1111/cea.12910